Potensi Kebangkrutan Pada Pra-Pandemi dan Masa Pandemi serta Pengaruhnya Terhadap Profitabilitas - Safura, Nurul; Putra, Sugih Sutrisno (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2022)
This study aims to identify the potential for bankruptcy in the tourism and recreation industry listed on the IDX in the pre-pandemic and pandemic periods and its effect on profitability. The potential for bankruptcy in this research was measured by the modified Altman Z-Score model, while profitability was measured by return on assets. The research method used is quantitative research with a descriptive-associative approach. The source of data in this study uses secondary data in the form of the company's annual financial statements. The data analysis technique used a modified Altman Z-Score model, panel data regression analysis, classical assumption test, and hypothesis testing. The calculation results show that in the pre-pandemic, on average, the tourism and recreation industry companies were in the safe category with healthy financial conditions, while during the pandemic, the average company was in the gray category with a condition prone to bankruptcy. Based on the result of tests, the potential for bankruptcy has a significant effect on profitability. The greater potential for bankruptcy will affect the smaller profitability value and otherwise, the smaller bankruptcy potential will affect the greater profitability value.